Survey on Organizational Effectiveness In India: Exploring the Effectiveness of Organizations in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Any organization, commercial, industrial oreducational comes into existence when a group of people join hands forattainment of certain common objectives. Historians have evidence that inancient Egypt, a permanent work force of several thousand skilled workers wasfound to have built the pyramids (Romer, 2007). Similarly, the emperors ofChina used organizations a thousand years ago to construct its great irrigationsystem (Needham, 1986). As such, it is safe to say that organizations are notnew inventions. What is relatively new is the formal study and investigation oforganizations-how they work, what makes them effective, their pitfalls, andways that they can be managed and improved.